United Republic of Tanzania : Fourth Review Under the Policy Support Instrument and Request for an Arrangement Under the Standby Credit Facility: Staff Report; Debt Sustainability Analysis; Press Release on the Executive Board Discussion; and Statement by the Alternate Executive Director for The United Republic of Tanzania. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Tanzania's economy experienced adverse supply shocks in 2011. The Fourth Review under the policy support instrument (PSI) discusses that tighter fiscal and monetary policies are addressing the inflationary impact of the drought/energy shock. Performance under the PSI-supported program has been generally satisfactory. All December 2011 and March 2012 quantitative assessment criteria and indicative targets were met, other than the March 2012 floor on net international reserves, which was missed on account of delays in contracting programmed external borrowing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet